The Effect of Skeletal Muscle Exercise on Body Immunity: A Literature Review on Inflammation and Immune Cell Response - Nur Fadillah; Muh. Rifki; Ani Sasmita; Sandi Inrawan; Iqra Bismi Rusli (International Journal of Experimental Sports Science Research, 2025)
Background: Skeletal muscle exercise has long been recognized as a physiological stimulus that not only influences physical capacity but also significantly modulates the immune system. However, a deep understanding of how exercise affects systemic inflammation and the responses of various immune cell populations including NK cells, T lymphocytes, neutrophils, monocytes, and macrophages continues to evolve and requires comprehensive synthesis. Objectives: This literature review aimed to systematically analyze the effect of skeletal muscle exercise on two main immunity domains: (1) regulation of systemic inflammation through biochemical markers, and (2) specific immune cell responses across different exercise modalities and intensities. Methods: Literature searches were conducted on PubMed, Scopus, Google Scholar, and ScienceDirect using keywords related to physical exercise, inflammation, and immune cells, limited to publications from 2015–2025. Twenty-five articles were selected based on PRISMA criteria for narrative analysis. Results: Moderate exercise consistently reduced pro-inflammatory markers (TNF-α, IL-1β, CRP) and increased anti-inflammatory markers (IL-10, IL-4, adiponectin). At the cellular level, moderate aerobic exercise increased NK cell cytotoxic activity by up to 65%, improved CD4+/CD8+ ratio, and enhanced phagocytic capacity of neutrophils and macrophages. Conversely, very high-intensity exercise without adequate recovery triggered transient immunosuppression characterized by lymphopenia, elevated cortisol, and decreased sIgA. Conclusions: Skeletal muscle exercise with appropriate intensity and volume constitutes a potent natural immunomodulator. Optimal exercise doses differ for optimizing inflammatory versus cellular immune responses and must be individualized.